A General Equilibrium Analysis of Climate Change Impacts on Tourism - Andrea Bigano; Maria Berrittella; Roberto Roson; Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper studies the economic implications of climate-change-induced variations in tourism demand, using a world CGE model. The model is first re-calibrated at some future years, obtaining hypothetical benchmark equilibria, which are subsequently perturbed by shocks, simulating the effects of climate change. We portray the impact of climate change on tourism by means of two sets of shocks, occurring simultaneously. The first shocks translate predicted variations in tourist flows into changes of consumption preferences for domestically produced goods. The second shocks reallocate income across world regions, simulating the effect of higher or lower tourists' expenditure. Our analysis highlights that variations in tourist flows will affect regional economies in a way that is directly related to the sign and magnitude of flow variations. At a global scale, climate change will ultimately lead to a welfare loss, unevenly spread across regions.
Keywords: D58; L83; Q51; Q54; 330; Climate change; Computable general equilibrium models; Tourism; Klimawandel; Tourismus; Allgemeines Gleichgewicht; Simulation; Welt